Construction of Highly Ordered Glyco‐Inside Nano‐Assemblies through RAFT Dispersion Polymerization of Galactose‐Decorated Monomer. Issue 20 (25th March 2021) - Qiu, Liang; Zhang, Haoran; Bick, Thomas; Martin, Johannes; Wendler, Petra; Böker, Alexander; Glebe, Ulrich; Xing, Chengfen
Abstract: Glyco‐assemblies derived from amphiphilic sugar‐decorated block copolymers (ASBCs) have emerged prominently due to their wide application, for example, in biomedicine and as drug carriers. However, to efficiently construct these glyco‐assemblies is still a challenge. Herein, we report an efficient technology for the synthesis of glyco‐inside nano‐assemblies by utilizing RAFT polymerization of a galactose‐decorated methacrylate for polymerization‐induced self‐assembly (PISA). Using this approach, a series of highly ordered glyco‐inside nano‐assemblies containing intermediate morphologies were fabricated by adjusting the length of the hydrophobic glycoblock and the polymerization solids content. A specific morphology of complex vesicles was captured during the PISA process and the formation mechanism is explained by the morphology of its precursor and intermediate. Thus, this method establishes a powerful route to fabricate glyco‐assemblies with tunable morphologies and variable sizes, which is significant to enable the large‐scale fabrication and wide application of glyco‐assemblies. Abstract : Glyco‐inside nano‐assemblies containing numerous intermediate morphologies are fabricated by leveraging RAFT polymerization of a galactose‐decorated monomer for polymerization‐induced self‐assembly. This method establishes a powerful route to fabricate glyco‐inside nano‐assemblies with tunable morphologies and variable sizes, which is significant to expand the large‐scale fabrication and wide application of glyco‐assemblies.